Developing guidelines for local role-players to implement the school-based Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome prevention programme in Bushbuckridge Mpumalanga - Peu, Mmapheko Doriccah (University of Pretoria, 2018)
Preventing new HIV infections and AIDS-related deaths are at the heart of South Africa’s new National Strategic Plan on HIV and AIDS, STIs and TB 2012-2016. Following from this strategy, a number of interventions were designed and developed by the government including the Integrated School Health Policy 2012 to prevent new HIV infections and improve the health of children and youth of school-going age. Mpumalanga is the province with the second highest HIV prevalence levels of 34.6%. Particularly, Bushbuckridge Municipality is said to have a higher prevalence of HIV and AIDS than other Municipalities. Having an effective school-based HIV and AIDS prevention programme in these areas may reduce the HIV prevalence. Unfortunately, reports reflect that the education sector as well as health services in the area are under severe strain to meet the demands and challenges associated with the socioeconomic determinants of the HIV epidemic. The purpose of the study was to develop and describe guidelines for local role players to implement the HIV and AIDS prevention in local high school settings Bushbuckridge, Mpumalanga province. The study was guided by the following research question:  How will guidelines for the role-players to implement the HIV and AIDS prevention in local high school settings Bushbuckridge, Mpumalanga Province be developed? The specific objectives of the study were to:  Explore and describe the roles of the local role players in the implementation of the HIV and AIDS prevention programmes in local high school settings.  Explore and describe the challenges experienced by the local role players in the implementation of the HIV and AIDS prevention programme in local high school settings.  Develop and describe guidelines for local role players to implement the HIV and AIDS prevention in local high school settings Bushbuckridge, Mpumalanga province. The study was conducted in two phases. The first phase was the empirical phase where exploration and description of the roles of local role players in health teams regarding the implementation of the HIV and AIDS prevention programmes in school settings was done. In addition, the challenges experienced by local role players were explored and discussed. A qualitative, explorative, descriptive design and contextual study was conducted. Its qualitativeness offered the researcher an opportunity to uncover the coordination of services amongst and participation of the local role players to collaborate in ensuring efficient implementation of the HIV and AIDS programme in schools. The population constituted of the local role players who have a designated responsibility in school health teams in the Bushbuckridge area of Mpumalanga province. These role players included members of School Governing Bodies, local non-governmental organisations (NGOs), educators, local clinics, PHC nurses and the health district managers. Data was collected through semistructured focus groups and semi structured individual interviews. Verbatim transcription of the focus group discussions and individual interviews was done. Tesch’s method of data analysis was used to provide detailed guidance for the coding process and analysis. The Social Ecological Model was used as a framework to guide the discussion of the findings in relation to the multiple effects and interrelatedness of social elements in school-based HIV and AIDS prevention programmes. Three major themes were identified: the roles of the local role players, and the challenges as well as suggestions to the implementation of the school-based HIV and AIDS prevention programme. . Five major roles for the local role players were identified, viz; providing HIV and AIDS health services; giving HIV and AIDS education; ensuring collaboration (referral system) between role players and services; educators and nurses view of the programme and monitoring and evaluation of the programme. Educators were found to be key facilitators for the programme while nurses and the NGOs were involved as support and supplementary structures in the implementation of the school-based HIV and AIDS prevention programme. For the second theme, challenges experienced by the role players ranged from departmental challenges, lack of resources and personal barriers. The provision of adequate resources was found to be key to increasing the uptake of the programme. In Phase 2 the empirical evidence obtained in Phase 1 was used to formulate, develop and describe guidelines for local role players to implement HIV and AIDS prevention programmes in high school settings as a package of school health services. The Modified Delphi technique was used to refine the drafted guidelines. Experts from the health and education sectors, including those from HIV and AIDS prevention services from government and NGO sectors as well as health professionals in health promotion services, were used as participants in Phase 2. A three round modified Delphi was done to finalize the guidelines for role-players to implement the school based HIV and AIDS prevention programme in high schools. Six guidelines were developed and described; the custodians of the school-based HIV and AIDS prevention programme are to facilitate strengthening capacity building for the local role players (school health nurses, ward based outreach teams (WBOTs), educators, parents and NGOs) in relation to their roles in the implementation of the school-based HIV and AIDS prevention programme, the custodians of the school-based HIV and AIDS prevention programme are to foster participation and involvement of other local role players (school health nurses, primary healthcare (PHC) nurse, educators, parents and NGOs) in an effort to embrace cultural diversity and enhance the programme uptake within the individual’s frame of reference, the custodians of the school-based HIV and AIDS prevention programme are to facilitate multi-sectorial collaboration among the local role players, and forming partnerships with key stakeholders from relevant government and non-governmental sector(s) within the different levels, the custodians of the school-based HIV and AIDS prevention programme with the local role players are to promote the implementation of the school-based HIV and AIDS prevention programme, the custodians of the school-based HIV and AIDS prevention programme together with the local role players must have full access to all policies, especially those related to the school-based HIV and AIDS prevention programme to guide them through the implementation of the programme and the custodians of the school-based HIV and AIDS prevention programme together with the local role players are to develop clear and easily accessible school-based surveillance systems to be implemented by all the local role players to track, monitor and evaluate the progress and impact of the programme including the general practices.These guidelines may form part of the HIV and AIDS prevention programme. Successful development and implementation of the school-based HIV and AIDS prevention programme can result in significant changes in knowledge and attitudes that affect sexual behaviour of young people, leading to significant decreases in HIV infection among young people. The findings of this study are applicable to the context of this study, in the same breathe can be transferable in similar context.